Shoulder Physiological Offset Parameters in Asian Populations—A Magnetic Resonance Imaging Study - Hung-Yi Huang; Meng-Hao Lin; Chu-Hsiang Hsu; Liang-Tseng Kuo (Diagnostics)
Background/Objectives: Physical shoulder offset parameters (SOPs) play important roles in the diagnosis and treatment of shoulder diseases. However, there is little research analyzing SOPs in healthy shoulders using cross-sectional MRI images, especially in Asians. Therefore, this study aimed to establish physiological reference values of shoulder parameters for Asian populations. Methods: This was a retrospective imaging study using MRI images of the shoulder joints of 500 patients (mean age: 55.9 ± 14.0 years). We measured the following SOPs of the normal joint: HO, GO, lateral glenoidal humeral offset (LGHO), humeral shaft axis offset (HAO), and cortical offset (CO). In addition, the offset parameters were examined for associations with age, gender, side, and osteoarthritis. Results: The mean HO was 22.9 (±2.4) mm, the mean GO was 62.3 (±6.6) mm, the mean LGHO was 48.9 (±4.2) mm, the mean HAO was 25.2 (±2.8) mm, and the mean CO was 15.7 (±2.7) mm. Male patients exhibited significantly higher values across all SOPs compared to female patients. In addition, there was a significantly lower mean value for HAO in left shoulders (HAO: 24.7± 2.8 mm vs. 25.5 ± 2.8 mm, p = 0.011). There was a negatively significant correlation between age and all SOPs. No significant difference in mean values was noted between shoulders with osteoarthritis and non-osteoarthritis in any SOPs. Conclusions: Significant gender- and age-specific differences were noted for all measured SOPs. In addition, right shoulders did not show higher mean SOP values than left shoulders, except for HAO, suggesting that the contralateral joint is a reliable reference for surgical planning. These findings should be considered in shoulder surgery planning.